The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1116/1.2835091
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of titanyl phthalocyanine in thin films prepared by surface polymerization by ion-assisted deposition

Abstract: Surface polymerization by ion-assisted deposition (SPIAD), the simultaneous dosing of hyperthermal ions while depositing an organic oligomer, was used to deposit titanyl phthalocyanine (TiOPc) thin films with 50 and 100 eV acetylene ions. The properties of the SPIAD TiOPc thin films are compared with films of the evaporated TiOPc monomer via examination of the electronic structure, ultraviolet-visible absorbance, and composition. Mass spectrometry, x-ray photoelectron spectroscopy, and other methods were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…This is not surprising considering that TiOPc in its "bulk" form adopts a double layer structure. 31,32 Furthermore, the absence of a clear shakeup structure for the peak at higher binding energy is in line with a charge reduction in the HOMO. This is also supported by the disappearance of the HOMO feature in valence band spectra from 1 ML TiOPc (Figure 5b).…”
Section: Resultsmentioning
confidence: 69%
“…This is not surprising considering that TiOPc in its "bulk" form adopts a double layer structure. 31,32 Furthermore, the absence of a clear shakeup structure for the peak at higher binding energy is in line with a charge reduction in the HOMO. This is also supported by the disappearance of the HOMO feature in valence band spectra from 1 ML TiOPc (Figure 5b).…”
Section: Resultsmentioning
confidence: 69%
“…Ion modification also increased the carbon content in the films and dissociated functional units of the 4T oligomers. The 50 eV ion beam consisted of ∼97% molecular ions denoted as C 2 H x + ( x = 0–2), ∼3% CH x + ( x = 0, 1), and an indeterminate amount of H x + ions, so the ion beam was modeled by C 2 H + ions. The simulations predicted that bond breakage in 3T oligomers as a result of the deposition of the ions is a critical step toward producing oligomer–PbS bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylene ions with 50 eV kinetic energy were generated by a Kaufman ion source (IBS 250, 3 cm, Veeco/Commonwealth Scientific, Plainview, NY) 15 and used to modify the films simultaneous with 4T and PbS cluster deposition. The ion source was mounted 45 from the surface normal.…”
Section: Experiments a Sample Preparationmentioning
confidence: 99%
“…10 The acetylene ions used in ion-assisted deposition behave both as catalysts and reagents by energetically inducing bonding between condensed phase species and forming adducts with the neutral reagents. [11][12][13][14][15] X-ray photoelectron spectroscopy (XPS) was employed to probe photoconductivity of the PbS nanoparticle-4T composite films. For insulating and semiconducting samples, it has been observed that surface charging can shift the measured binding energies in an X-ray photoelectron (XP) spectrum.…”
Section: Introductionmentioning
confidence: 99%